Pengaruh Terpaan Iklan Kredivo Versi Hidup #sefleksibelitu Terhadap Pengambilan Keputusan Dalam Bertransaksi Menggunakan Kredivo - Bion, Bion (Brand Communication, 2023)
Along with the development of the era where internet networks have become a primary need and smartphones have become important items, various manufacturers are now competing in making smartphone applications so that their products or services are used by many people. This also applies to the banking industry which gave birth to a new thing called financial technology (FinTech). The presence of FinTech then gave birth to new services and ways of doing transactions, namely transactions through credit applications and online loans. One of the FinTechs that provide these services is Kredivo, which was founded by PT FinAccel Teknologi Indonesia in 2016. One of the strategies used by Kredivo in promoting its products is to use advertising media. Kredivo through a campaign with the hashtag #Sefelksibelitu has launched several advertisements, one of which is 'Hidup #Seflexibelitu | Kredivo'. This advertisement has been watched by 29.2 million people on the Kredivo Youtube channel. This made researchers interested in knowing the effect of advertising exposure on the decision to make a transaction using Kredivo. The purpose of this research is to find out whether or not there is an effect of the #SeflexibleLife | Life advertisement Kredivo for making decisions on transactions using Kredivo. This research is quantitative research with a descriptive approach. Questionnaires with 9 differential semantic scales were distributed using a purposive sampling technique to 100 people who met the respondent's criteria. Then the results of the study were analyzed using a simple linear regression test. The results showed that exposure to Kredivo Hidup #Seflexibelitu advertising had a positive effect on the decision to make a transaction using Kredivo and the contribution was 19%.